The Use of Sterile Razors as an Efforts to HIV Transmission Prevention - Yuniar Wardani; Liena Sofiana; Suci Musvita Ayu; Erni Gustiina; Marsiana Wibowo; Fardhiasih Dwi Astuti; Septian Emma Dwi Jatmika (Intelektual Pustaka Media Utama, 2017)
HIV Transmission can also occur as a result of the employment relationship.In addition to health workers there are other workers who are in close contact with his client was a barber, hairdresser, masseur, tattoo, ear piercer and acupuncturist. The purpose of this study was to determine the behavior of a barber in the prevention of transmission of HIV/AIDS with the use of a sterile razor blade. The study design was cross-sectional survey and data analysis is performed simultaneously with quantitative descriptive approach. This study was conducted in the district of Yogyakarta Special Region of Yogyakarta. Subjects of the study were all traditional barber in the study area. The sampling technique used purposive sampling with certain criteria under the terms set by the researchers. The data analysis used Spearman. The average age of respondents was 30.91, the number of consumers 31.28. Mean knowledge is 34.09, attitudes and behavior amounting to 31.06. Based on the rate most people are able to reach a price set by a razor because the tariff ranges between IDR 6,000-10,000 and an average tariff of IDR 8,230. On average shaver have 32 customers each month. There was a correlation between knowledge, attitude with behavior of a barber in the prevention of transmission of HIV/AIDS. There was a correlation between knowledge, attitude and behavior to conduct barber in the prevention of transmission of HIV/AIDS.